AWARENESS OF RISK FACTORS OF OBESITY AMONG WOMEN - Taskeen. L, Tahoora; V. , Vishnu Priya; R. , Gayathri (International Journal of Psychosocial Rehabilitation, 2020)
Background: Obesity is a complex condition that has become more prevalent among women. As it is the need of the hour to detect the awareness of risk factors for obesity. Aim: To determine the awareness of risk factors for obesity among women. Materials and methods: Self-administered questionnaires were designed based on the awareness of risk factors for obesity among women. The questionnaire was distributed through an online survey on Planet Link; the study population included 100 women. The data was collected and statistically analyzed. Result and Discussion: Obesity raises the risk of many chronic diseases. Participants were mostly aware of the risk factors. Age, education, and other environmental factors are related to overweight and obesity. More awareness may be created to educate the society about the risk factors of obesity and its associated disorders.